THE ANALYSIS OF THE CHANGE IN GHRELIN LEVEL IN PATIENTS WITH DIFFERENT FORMS OF PARKINSON’S DISEASE - Tarianyk, K.А.; Kaidashev, I.P.; Shlykova, O.A.; Izmailova, O.V. (World of Medicine and Biology, 2020)
The aim of our study was to analyze diurnal fluctuations in hunger hormone level in patients with akinetic-rigid and mixed forms of Parkinson’s disease. The clinical studies have confirmed changes in the ghrelin level with a tendency to increase in the evening in patients of the control group and insignificant diurnal fluctuations in the level of ghrelin in patients with Parkinson’s disease with a tendency to decrease. It has been revealed that in patients with mixed form of the disease, the ghrelin level is lower compared to controls. The human circadian system regulates hunger independently of behavioral factors. There is a large endogenous circadian rhythm of hunger, with a peak in biological evening and a minimum in biological morning. However, the neuroendocrine mechanisms by which the circadian system regulates hunger and appetite remain unclear. Ghrelin, a peptide secreted primarily by the stomach, is the only known circulating orexigenic hormone and a key element in a complex energy balance signaling network. The authors insist that further clinical research is needed to determine the relationship between the intake of antiparkinsonian drugs and the ghrelin level, which can significantly improve the clinical course of this disease.
Keywords: Parkinson’s disease; ghrelin; circadian rhythms